Assessment of Anesthesia Practice Patterns for Endovascular Therapy for Acute Ischemic Stroke: A Society for Neuroscience in Anesthesiology and Critical Care (SNACC) Member Survey. Issue 4 (1st October 2021) - Rusy, Deborah A.; Hofer, Adam; Rasmussen, Mads; Paisansathan, Chanannait; Sharma, Deepak
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The choice of general anesthesia (GA) or conscious sedation (CS) may impact neurological outcomes of patients undergoing endovascular therapy (EVT) for acute ischemic stroke (AIS). The aim of this survey was to describe the practice patterns of members of the Society for Neuroscience in Anesthesiology and Critical Care (SNACC) for anesthetic management of AIS. Methods: Following institutional review board approval, a 16-question online survey assessing anesthetic management of patients with AIS undergoing EVT was circulated to members of SNACC. Results: A total of 76 SNACC members from 52 institutions and 11 countries completed the survey (12.5% response rate). Overall, 33% of institutions reported dedicated neuroanesthesia teams for EVT. Patients treated with GA ranged from 5% to 100% between centers. In total 51% and 49% of centers in the United States reported preferentially providing GA and CS, respectively, compared with 34% and 66%, respectively, in European centers. Reported anesthetic induction agents are propofol (64%), etomidate (4%) and either medication (33%). For maintenance of GA, volatile anesthetic is used more often (54%) than propofol (16%). There was wide variation in medications used for CS. Arterial catheter placement was reported by 75% and 43% of respondents for patients undergoing GA and CS, respectively. Systolic blood pressure >140 mm Hg was targeted by 35.7% of respondents, with others targeting mean arterial pressure within 10%, 20% or 30% of baseline values. Phenylephrine and norepinephrine were the most commonly used vasopressors. Conclusions: There is wide variation in anesthesia technique and hemodynamic management during EVT for AIS, and no consensus on the choice of, or preferred medications for, GA or CS, or target blood pressure and management of hypotension during the procedure.